Tanggap Pertumbuhan dan Produksi Kedelai Terhadap Pemberian Abu Vulkanik Sinabung Dan Pupuk Kandang Ayam - Daniel Marko; Jonatan Ginting; Jonis Ginting (Universitas Sumatera Utara, 2016)
The aim of research was to known the effect by application Sinabung volcanic ash and chicken manure. The research was done at Tanjung Sari Medan district (±25 meters from sea) form October 2014 until January 2015. It was used Randomized Block Design with two factorials Sinabung volcanic ash (0, 500, 1000, 1500, 2000 g / plot) and chicken manure (0, 500, 1000 g / plot) with three replicate. The result showed with application Sinabung volcanic ash was significant effect to steam diameters three week after planted, the numbers of pods seeds, the number of seed per plant, the seed weight per plant, yield of plant, the seed weight in one hundred. The chicken was significant effect to steam diameters three week after planted, the numbers of pods seeds, the number of seed per plant, the seed weight per plant, yield of plant, the seed weight in one hundred. The interaction with Sinabung volcanic ash and chicken manure was significant effect to steam diameters three week after planted, the numbers of pods seeds, the number of seed per plant, the seed weight per plant, yield of plant, the seed weight in one hundred.Keyword: Sinabung volcanic ash, chicken manure, soybean.